Keragaman Genetik Amfibia Kodok (Rana nicobariensis) di Ecology Park, Cibinong Berdasarkan Sekuen DNA dari Mitokondria d-loop - Astuti, Dwi; Kurniati, Hellen (JURNAL BIOLOGI INDONESIA, 2010)
ABSTRACTGenetic Diversity of Amphibia (Rana nicobariensis) at Ecology Park, Cibinong Based onDNA Sequences of Mitochomndrial d-Loop. The 397- base pairs from ten nucleotide sequencesof mitochondrial d-loop region were determined and analyzed in object to study the geneticdiversity of frog Rana nicobariensis at Ecology Park, Cibinong, West Java. There were sixhaplotypes from 10 individuals collected from Ecology Park. Haplotype and nucleotide oramino acid diversities in Ecology Park were 0.964 and 0.0064 respectively.Key words: Genetic diversity, Rana nicobariensis, Ecology Park Cibinong, DNA sequences,mitochondrial-d-loop